Syndrome of inappropriate antidiuretic hormone as the initial presentation in Guillain-Barré syndrome - Divya Asti; Nicholas Fuca; Jiyoung Wong; Bindu Madhavi Mudduluru; Elie El-Charabaty (Society of Diabetic Nephropathy Prevention, 2018)
Background: Guillain-Barré syndrome (GBS) is an autoimmune disease damaging the peripheral nervous system. It commonly presents as rapidly progressing bilateral symmetrical motor weakness. There has been known association of syndrome of inappropriate antidiuretic hormone (SIADH) in patients with GBS though it is rare. Case Presentation: We report a patient with rare clinical presentation of SIADH before the onset of motor deficits in GBS. Conclusions: SIADH as an initial finding in patients with GBS is very rare. This case report emphasizes the importance of early detection of SIADH in GBS to avoid delay in treatment.